Bridging the Digital Divide: Senior Chinese Immigrants’ Experiences with Health Technologies in Canada (The Journal of Medicine, Humanity and Media, 2025)
The global aging population is increasingly impacted by the digital divide, which affects their quality of life and access to services. Chinese senior immigrants in Canada face great challenges navigating digital environments due to language barriers, cultural adaptation issues, and limited access to digital resources. Using Cultural-Historical Activity Theory (CHAT) as a theoretical framework, this study explores the key factors of the digital divide among Chinese senior immigrants, challenges of their use of health-related technologies, and their strategies in adapting to these digital tools. Through semi-structured, in-depth interviews with 9 Chinese senior immigrants in Canada, this study argues that the digital divide is not merely an issue of technological access but a socially situated, culturally mediated, and historically developed phenomenon shaped by social structures, community supports, learning, and well-being. By framing digital literacy as a socially situated and developmental process, this study contributes to health communication by proposing a Cross-Cultural Digital Health Literacy Nexus (CDHLN) that enhances cross-cultural digital health engagement, improves senior immigrants' access to health information, and promotes well-being among aging immigrant populations.
Keywords: Digital Divide; Chinese Senior Immigrants; Cross-cultural Communication; Health Technologies; Digital Literacy Learning